Effect of exopolysaccharides-producing strain on oxidation stability of DHA micro algae oil microcapsules. (June 2018) - Liu, Lu; Qu, Xiuwei; Li, Xiaodong; Massounga Bora, Awa Fanny; Chen, Ping; Wang, Haixia; Wang, Chunchao
Abstract: DHA micro algae oil was encapsulated in whey protein isolate (WPI)-gum Arabic (GA) by complex coacervation and added exopolysaccharides (EPS)-producing strain to increase the emulsion and the oxidation stability of micro algae oil microcapsules. The physicochemical properties and the oxidative stability of microcapsules were investigated. The microcapsules with EPS ++ strain had excellent emulsion stability, acceptable particle size (25.83 µm) and the highest encapsulation efficiency (92.5%) which were further confirmed by the uniform surface structure evidenced by the scanning electro microscope. Moreover, the EPS ++ strain exhibited a protective effect on oxidation stability of microcapsules during storage with the lowest content of peroxide (PV), headspace propanal and p-anisidine (p-AV). Therefore, the EPS- producing strain can be used as potential wall material to improve the oxidation stability of DHA micro algae oil. Graphical abstract: Highlights: Micro algae oil and EPS strain were effectively co-encapsulated in WPI-GA complex coacervate. The physicochemical properties of microcapsule with EPS strain were excellent. EPS strain could protect micro algae oil against oxidation during the storage.